Public attitudes toward stuttering in Poland. Issue 6 (2nd August 2013) - Przepiorka, Aneta M.; Blachnio, Agata; St. Louis, Kenneth O.; Wozniak, Tomasz
Abstract: Background: People who stutter often experience negative judgments and reactions to their stuttering from the nonstuttering majority. Many are stigmatized because of their stuttering and threatened with social exclusion, placing them at risk for compromised quality of life. Aims: The purpose of this investigation was to measure public attitudes toward stuttering in Poland. Methods & Procedures: A sample of 268 respondents (mean age = 29 years; range = 15–60 years) from numerous different geographic and urban‐rural settings in Poland filled out a Polish translation of the Public Opinion Survey of Human Attributes–Stuttering ( POSHA–S ). Outcomes & Results: Polish respondents displayed attitudes toward stuttering and people who stutter that were generally similar or "average" in comparison with other samples around the world from the POSHA–S database. Conclusions & Implications: Although generally typical of other Western societies studied, attitudes of adolescents and adults from Poland were notably different in some ways, such as in the beliefs that emotional trauma or viruses and disease can cause stuttering as well as in the self reaction that they would feel uncomfortable speaking with a stuttering person. Overall, social exclusion and stigma are as likely among Poles who stutter as among most other populations studied.